Perinatal HIV Infection or Exposure Is Associated With Low N-Acetylaspartate and Glutamate in Basal Ganglia at Age 9 but Not 7 Years - Robertson, Frances C.; Holmes, Martha J.; Cotton, Mark F.; Dobbels, Els; Little, Francesca; Laughton, Barbara; van der Kouwe, André J. W.; Meintjes, Ernesta M. (Frontiers in Human Neuroscience, 2018)
Abnormalities of the basal ganglia are frequently seen in HIV-infected (HIV+) children despite antiretroviral treatment (ART) initiation during childhood. Assessment of metabolites associated with neuronal integrity or with glial proliferation can present a sensitive description of metabolic events underlying basal ganglia structural changes. We used magnetic resonance spectroscopy to examine differences in creatine, choline, N-acetylaspartate (NAA), glutamate and myo-inositol between HIV+ children and HIV-unexposed controls, as well as between HIV-exposed uninfected (HEU) children and HIV-unexposed controls at age 7 and at age 9. No differences in metabolites relative to the HIV-unexposed control group were found at age 7. However, at 9 years, both HIV+ and HEU had lower NAA and glutamate than unexposed control children. HEU children also had lower creatine and choline than control children. At age 7, lower CD4/CD8 ratio at enrollment was associated with lower choline levels. At age 9 lower CD4/CD8 at enrollment was associated with lower myo-inositol. Low NAA and glutamate at age 9, but not 7, suggest that basal ganglia neurons may be particularly affected by perinatal HIV/ART and that neuronal damage may be ongoing despite early ART and viral suppression. Reduced basal ganglia metabolite levels in HEU children suggest an effect of HIV exposure on childhood brain development that merits further investigation using neuroimaging and neurocognitive testing.